Comprehensive behavior management : individualized, classroom, and schoolwide approaches - Martella, Ronald C.; Martella, Ronald C.; Nelson, J. Ron.; Marchand-Martella, Nancy E.; O'Reilly, Mark. (Los Angeles : SAGE, 2012)
'Comprehensive Behavior Management: Schoolwide, Classroom, and Individualized Approaches supports teachers in preventing management problems and responding to unwanted behavior when it occurs in classrooms. The text offers a comprehensive presentation of three levels of behavior management strategies: school-wide, classroom, and individual, all three of which contribute to a positive learning environment. A social learning emphasis, in which human behavior is viewed within an ecological framework, is integrated throughout the text. Application of this information is supported by a range of devices such as vignettes, examples, strategies, and activities to show teachers how to manage behavior effectively'--
Machine generated contents note: Part One: Introduction to Behavior ManagementChapter 1: Behavior Management ModelsChapter 2: The Foundations Of Behavior ManagementPart Two: Individualized Behavior SupportsChapter 3: Pinpointing And Tracking A Behavior ProblemChapter 4: Functional Behavior Assessments And Behavior Support PlansChapter 5: Increasing Desirable BehaviorsChapter 6: Decreasing Undesirable BehaviorsPart Three: Classroom SupportsChapter 7: Preliminary ConsiderationsChapter 8: Instructional VariablesPart Four: School-Wide SupportsChapter 9: School SafetyChapter 10: Positive Behavior Intervention And SupportChapter 11: Evidence-Based Interventions and ProgramsChapter 12: Response to Intervention (RTI) and School-Wide Positive Behavior Intervention Supports (SWPBIS) ModelsGlossaryReferencesIndex.
Rev. ed. of: Managing disruptive behaviors in the schools : Boston : Allyn and Bacon, c2003.
Includes bibliographical references (p. 407-419) and index.
Keywords: Classroom management; Behavior modification